Properties of concrete containing eggshell powder as partial cement replacement - Tan, Yeong Yu (2018)
The increasing of the greenhouse effect and carbon dioxide by the cement manufacturing industry as well as solid waste disposal have caused negative impact to the environment. Besides, the consumption of eggs in Malaysia is very high which is 300 eggs per person annually. Thus, the dumping of the eggshell at the site generates stinky smell and attracts worms and rat due to its high protein membrane of the eggs. Utilization of the eggshell as partial cement replacement in producing concrete would reduce the cement consumption and amount of waste disposed. Thus, this research was conducted to investigate the characteristics of eggshell, mechanical properties and durability performance of eggshell concrete. Two different drying conditions of eggshells were used as partial cement replacements which are air-dried and oven-dried. The characteristic of the eggshell was examined by X-Ray diffraction (XRD), X-Ray fluorescence (XRF), scanning electron microcopy (SEM) and fourier transform infrared spectroscopy (FTIR). At the early stage of the research, trial mix was conducted to identify the optimum water-cement ratio. A control specimen and eggshell concrete was cast into (100 x 100 x 100) mm cube, (100 x 100 x 500) mm beam and (dia. 100 x 300) mm. The effect of the curing method namely water curing and air curing. The compressive strength, flexural strength and splitting tensile strength of the concrete specimens have been examined. Experiments on the durability performance of the concrete specimens is water absorption. Besides, the eggshell concrete was placed in both acid solution and alkali solution to identify the performance eggshell concrete under aggressive solution. The findings show that the water curing with 15% of oven-dried eggshell concrete had the highest compressive strength, flexural strength and splitting tensile strength. Water curing promotes a better hydration process that improve the internal structures and exhibit lower water absorption. Thus, care should be taken when acid and alkali environment as calcium is the primary component to be react with the acid and alkali solution. Finally, the study showed that concrete that containing eggshell has the potential to be used as structural application.